2010
DOI: 10.1136/tc.2009.032599
|View full text |Cite
|
Sign up to set email alerts
|

‘Acceptable rebellion’: marketing hipster aesthetics to sell Camel cigarettes in the US

Abstract: Objective The aim of the present work was to understand why and how RJ Reynolds and other tobacco companies have marketed tobacco products to young adult social trendsetting consumers (termed ‘hipsters’) to recruit trendsetters and average consumers to smoke. Methods Analysis of tobacco industry documents and industry marketing materials. Results Since 1995, RJ Reynolds developed its marketing campaigns to better suit the lifestyle, image identity and attitudes of hip trendsetters (so-called ‘hipsters’), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 56 publications
0
42
0
1
Order By: Relevance
“…Additionally, message boards are only one of many features on tobacco brand websites that might work to cultivate tobacco use and brand loyalty. These brand websites may include games, creative online contests, sweepstakes that can be entered daily for ‘improved’ chances at winning, entertaining videos or photo galleries and free gift and coupon offers 26 27. Continued surveillance of these current and dynamic forms of tobacco advertising is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, message boards are only one of many features on tobacco brand websites that might work to cultivate tobacco use and brand loyalty. These brand websites may include games, creative online contests, sweepstakes that can be entered daily for ‘improved’ chances at winning, entertaining videos or photo galleries and free gift and coupon offers 26 27. Continued surveillance of these current and dynamic forms of tobacco advertising is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco companies have long used categories defined by psychographic factors or cultural affiliation (such as Hipster or Hip Hop culture) for targeted marketing campaigns. [23][24][25] Peer crowd affiliation is one innovative way to approximate psychographic and cultural segmentation to identify high-risk subgroups among young adult bar patrons. 14 'Peer crowds' are the macro-level connections between peer groups with similar values, interests, lifestyles, styles of dress, media consumption habits, influencers and social tendencies (eg, Hipsters).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings document name generation efforts and strategies utilised to collect names and targeting information for the databases, and add to the literature concerning targeting of individuals in priority groups. Previous research has shown direct mail campaigns targeting women, 48 young adults, 49 hipsters, 50 older smokers 51 52 and low SES females. 52 It has also been utilised to facilitate viral marketing of Eclipse cigarettes 53 and promote menthol cigarettes to young urban Blacks.…”
Section: Discussionmentioning
confidence: 99%